Maternal haemodynamic function differs in pre‐eclampsia when it is associated with a small‐for‐gestational‐age newborn: a prospective cohort study. (14th May 2020) - Perry, H; Binder, J; Gutierrez, J; Thilaganathan, B; Khalil, A
Abstract : Objective: To describe maternal haemodynamic differences in gestational hypertension with small‐for‐gestational‐age babies (HDP + SGA), gestational hypertension with appropriate‐for‐gestational‐age babies (HDP‐only) and control pregnancies. Design: Prospective cohort study. Setting: Tertiary Hospital, UK. Population: Women with gestational hypertension and healthy pregnant women. Methods: Maternal haemodynamic indices were measured using a non‐invasive Ultrasound Cardiac Output Monitor (USCOM‐1A ® ) and corrected for gestational age and maternal characteristics using device‐specific reference ranges. Main outcome measures: Maternal cardiac output, stroke volume, systemic vascular resistance. Results: We included 114 HDP + SGA, 202 HDP‐only and 401 control pregnancies at 26–41 weeks of gestation. There was no significant difference in the mean arterial blood pressure (110 versus 107 mmHg, P = 0.445) between the two HDP groups at presentation. Pregnancies complicated by HDP + SGA had significantly lower median heart rate (76 versus 85 bpm versus 83 bpm), lower cardiac output (0.85 versus 0.98 versus 0.97 MoM) and higher systemic vascular resistance (1.4 versus 1.0 versus 1.2 MoM) compared with control and HDP‐only pregnancies, respectively (all P < 0.05). Conclusion: Women with HDP + SGA present with more severe haemodynamic dysfunction than HDP‐only. Even HDP‐only pregnancies exhibit impaired haemodynamic indices compared with normal pregnancies, supporting a role of the maternal cardiovascular system in gestational hypertension irrespective of fetal size. Central haemodynamic changes may play a role in the pathogenesis of pre‐eclampsia and should be considered alongside placental aetiology. Tweetable abstract: Hypertensive disorders of pregnancy are associated with worse maternal haemodynamic function when associated with small‐for‐gestational‐age birth. Tweetable abstract: Hypertensive disorders of pregnancy are associated with worse maternal haemodynamic function when associated with small‐for‐gestational‐age birth.